2016
DOI: 10.1128/jvi.01829-15
|View full text |Cite
|
Sign up to set email alerts
|

C-5-Modified Tetrahydropyrano-Tetrahydofuran-Derived Protease Inhibitors (PIs) Exert Potent Inhibition of the Replication of HIV-1 Variants Highly Resistant to Various PIs, including Darunavir

Abstract: We identified three nonpeptidic HIV-1 protease inhibitors (PIs), GRL-015, -085, and -097, containing tetrahydropyrano-tetrahydrofuran (Tp-THF) with a C-5 hydroxyl. The three compounds were potent against a wild-type laboratory HIV-1 strain (HIV-1 WT ), with 50% effective concentrations (EC 50 s) of 3.0 to 49 nM, and exhibited minimal cytotoxicity, with 50% cytotoxic concentrations (CC 50 ) for GRL-015, -085, and -097 of 80, >100, and >100 M,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 59 publications
(86 reference statements)
2
25
0
Order By: Relevance
“…[17] These resistant variants are highly resistant to all currently approved PIs, including DRV and nucleoside reverse transcriptase inhibitors such as tenofovir. [17, 23, 39] Antiviral IC 50 values were determined using the p24 assay, and the results are listed in Table 2. As observed in our investigation, ATV failed to block the replication of these DRV-resistant HIV-1 variants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] These resistant variants are highly resistant to all currently approved PIs, including DRV and nucleoside reverse transcriptase inhibitors such as tenofovir. [17, 23, 39] Antiviral IC 50 values were determined using the p24 assay, and the results are listed in Table 2. As observed in our investigation, ATV failed to block the replication of these DRV-resistant HIV-1 variants.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that DRV potently inhibited the dimerization of HIV-1 protease monomer subunits. [39, 40] This was demonstrated by a fluorescence resonance energy transfer (FRET)-based HIV-1 expression assay. [15] The majority of other PIs do not show dimerization inhibitory activity.…”
Section: Resultsmentioning
confidence: 99%
“…GRL-084-13 and GRL-087-13 were fit using ARP/wARP (55)-Ligands (56) through CCP4. The initial coordinates for both GRL-084-13 and GRL-087-13 were prepared by modifying the coordinates of GRL-0476 taken from X-ray crystal structure of PR WT -GRL-0476, PDB code 5COK (57). Solvent molecules were fit using ARP/wARP-Solvent through CCP4.…”
Section: Determination Of Viral Growth Kinetics Of Cns-targeting Pi-rmentioning
confidence: 99%
“…Two nonpeptidic PIs, GRL-0476 and GRL-1398, and their properties were previously published (11,12), while GRL-037 and GRL-044 were newly designed and synthesized. The method of synthesis of GRL-037 and GRL-044 will be published elsewhere by A. K. Ghosh et al DRV was synthesized as previously described (7).…”
Section: Antiviral Agentsmentioning
confidence: 99%